How do Accessibility and Environmental Factors Influence Land Values? a Hedonic Price Analysis - Diva Kamilasari; Endah Saptutyningsih (Dinasti International Journal of Economics, Finance & Accounting, 2025)
Land is the basis for infrastructure and agriculture and is crucial to economic growth. The factors influencing land prices, in Magelang Regency, Indonesia, are investigated in this study. This study examines the effects of land productivity, land area, environmental conditions, and distance to major infrastructure (village center, trade area, and city center) on land value using a hedonic price model. The results indicate that while land area and distance to the center city does not have a statistically significant impact on land prices, land productivity, other accessibility, and environmental factors do. Due to the growing demand for land with significant economic potential, proximity to economic centers particularly important village roads and city centers plays a significant role in determining land value. Moreover, there is a significant connection between land prices and environmental parameters like temperature, indicating the growing significance of environmental quality in land prices. In order to guarantee sustainable land market development, these findings emphasize the necessity of incorporating economic, environmental, and geographical aspects into land valuation systems. This study highlights the necessity of strategic land use regulations to balance equitable land distribution, environmental sustainability, and economic development, offering valuable information to politicians and urban planners.